Factors Associated with Adolescent Pregnancy in Sub-Saharan Africa during the COVID-19 Pandemic: A Review of Socioeconomic Influences and Essential Interventions - Kons, K.; Biney, A.A.E.; Sznajder, K. (International Journal Of Sexual Health, 2022)
Objective: A literature review was conducted to analyze the impact of COVID-19 on documented preexisting determinants of adolescent pregnancy in sub-Saharan Africa, such as poverty, inequitable gender norms, low access to education, and reproductive health services. Methods: The terms “sub-Saharan Africa,” “Gender Norms,” “Poverty,” and “Adolescent Pregnancy” were used to search the literature for preexisting determinants of adolescence pregnancy in academic and grey literature. “COVID-19” was added to investigate the potential consequences of the pandemic. The literature revealed similar experiences in adolescents girls during the Ebola outbreak, which led to the analysis of government and healthcare official responses to previous epidemics. Results: The literature review revealed that the relationship between identified micro (inequitable gender norms, transactional sex, sexual and gender-based violence, early marriage, and menstruation) and macro (poverty, education, and healthcare factors contributing to adolescent pregnancy were exacerbated by the COVID-19 pandemic. Conclusion: Three realistic targets, including expanding and communicating available reproductive health resources, prioritizing the role of women in the economy, and ensuring return to school, should be included as part of current COVID-19 mitigation programs. Additionally, these interventions should be incorporated in future public health preparedness plans to reduce the risk of adolescent pregnancy during public health emergencies.
Research Article
Keywords: poverty; inequity; COVID-19